5-Hydroxytryptamine3 receptor antagonists and cardiac side effects. (October 2014) - Brygger, Louise; Herrstedt, Jørn
<x xml:space="preserve">Abstract</x> Introduction: 5-Hydroxytryptamine3-receptor antagonists (5-HT3-RA) are the most widely used antiemetics in oncology, and although tolerability is high, QTC prolongation has been observed in some patients. Areas covered: The purpose of this article is to outline the risk of cardiac adverse events (AEs) from 5-HT3-RAs, with focus on the three most commonly used, ondansetron, granisetron and palonosetron. Expert opinion: Most of the studies analyze electrocardiogram (ECG) changes after 5-HT3-RA administrations in healthy, young adults, or in noncancer patients to treat postoperative nausea and vomiting (PONV). Only a few studies have addressed ECG changes in cancer patients treated for chemotherapy-induced nausea and vomiting (CINV). Investigations in cancer patients are essential, because these patients are older and have a higher incidence of comorbidity, than those usually included in clinical trials. Furthermore, polypharmacy is frequent and drug–drug interactions between chemotherapy and other QTc-prolonging drugs may influence the pharmacokinetics and pharmacodynamics of the 5-HT3-RAs. During the next 10 – 15 years a huge increase in the number of cancer patients is expected, primarily in the group of 65-plus-year old. Therefore it will be crucial to address the incidence of cardiac AEs in cancer patients with known heart disease receiving chemotherapy and a 5-HT3 RA for the prophylaxis of CINV.